POWER DISCOURSE OF SEXUALITY IN SHORT STORIES TITLED MATA TELANJANG (2014) BY DJENAR MAESA AYU AND USHA MY THIRD CHILD (2007) BY SUCHEN CHRISTINE LIM - Nailul Ulah Al-Chumairah, (IJLECR (International Journal of Language Education and Cultural Review), 2019)
The concept of Michel Foucault power of sexuality perspective has strategic unities. This research uses the genealogy approach of power perspective by Michel Foucault. In this case to dissect relations and effects that arise from the relation of each discourse of sexuality power in the short stories of Mata Telanjang written by Djenar Maesa Ayu and Usha My Third Child written by Suchen Christine Lim. Based on the research that will be conducted, the researcher found 1) Relation of Power Discourse of Sexuality with Economic Practice, Household (Marriage), and Environmental System. 2) The Relationship of Power Discourse of Sexuality with Body Hysterization Through Medical Practice, and 3) The Relationship of Sexuality Powers Towards Teenage Girl. Keywords: Critical Discourse Analysis (CDA), genealogy, power, literature, sexuality